French Translation and Adaptation of the Lasater Clinical Judgment Rubric: A Multicentre Study (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2021)
Background: The clinical judgment of nursing graduates who begin practising is rarely fully adequate in situations requiring acute and critical care. Facilitating their clinical judgment development while they are learning is thus essential.Study objective: To produce a French-language version of an existing instrument for assessing the development of clinical judgment, based on translation and validation efforts in various French-speaking regions.Method: International multicentre study. Five-step transcultural translation and validation process: 1) selection of a valid and reliable English-language instrument; 2) reverse translation; 3) committee review of the translated instrument; 4) pre-testing of the translated instrument; and 5) test-retest reliability study.Results: The Lasater Clinical Judgment Rubric® has proven to be an apt instrument for reporting on the development of clinical judgment thanks both to its conceptual model and its metrological characteristics. Participants from Québec, Ontario, Manitoba, New Brunswick, Switzerland, France, and Belgium took part in the pre-testing (n = 16) and test-retest (n = 35) phases. The terms that proved most difficult to translate included expected patterns, patterns in data, being skillful, prompting, and commitment. Cronbach’s alpha coefficients were all greater than 0.84. In addition, all test-retest intraclass correlation coefficients were above 0.81.Conclusions: New nurses in professional practice need to have well-developed capabilities to manage the diversity and complexity of clinical situations. The French-language version of the Lasater Clinical Judgment Rubric defines the trajectory of clinical judgment development and describes the Tanner Model in concrete terms; it also facilitates communication and understanding of expectations for student performance. In clinical simulations, the Rubric may be used as a guide for debriefing, providing feedback, and encouraging reflective practice.